Helping pregnant women make better decisions: a systematic review of the benefits of patient decision aids in obstetrics. Issue 2 (21st December 2011) - Say, Rebecca; Robson, Stephen; Thomson, Richard
Abstract : Objectives: Patient decision aids can be used to support pregnant women engaging in shared decisions, but little is known about their effects in obstetrics. The authors aimed to evaluate the effects of patient decision aids designed for pregnant women on clinical and psychosocial outcomes. Design: Systematic review. Data on all outcomes were extracted and summarised. All studies were critically appraised for potential sources of bias and, when possible to obtain, the reported decision aids were evaluated. Meta-analysis was not possible due to the heterogeneity of outcomes in primary studies and the small number of studies. Data sources: Electronic searches were performed using Medline, Embase, the Cochrane Library and Medion databases from inception until December 2010. Reference lists of all included articles were also examined and key experts contacted. Eligibility criteria for selecting studies: Eligibility criteria included randomised controlled trials, which reported on patient decision aids for women facing any treatment decision in pregnancy published in English. Studies evaluating health education material that did not address women's values and preferences were excluded. Results: Patient decision aids have been developed for decisions about prenatal testing, vaginal birth after Caesarean section, external cephalic version and labour analgesia. Use of decision aids is associated with a number of positive effects including reduced anxiety, lower decisional conflict, improved knowledge, improved satisfaction and increased perception of having made an informed choice. Conclusions: Patient decision aids have the potential to improve obstetric care. However, currently the evidence base is limited by the small number of studies, the quality of the studies and because they involved heterogeneous decision aids, patient groups and outcomes.